CARBON PASTE ELECTRODE MODIFIED MOLECULARLY IMPRINTED POLY(METHYL RED) FOR VOLTAMMETRIC DETERMINATION OF CHLORAMPHENICOL - DEWI (NIM : 20513082), LISNA
Chloramphenicol (CAP) is a broad-spectrum antibiotic which is effective againts variety of gram-positive and gram-negative bacteria. This drug has been used for the treatment of childhood meningitis and thypoid fever. CAP has been used in veterinary practice for the prevention and treatment of many bacterial infections. However, it is well-known that CAP has serious side-effects on human beings such as gray baby syndrome, leukimia, and aplastic anemia. Thus, it is important to develop sensitive and selective methods for the determination CAP in pharmaceutical products. Several analytical methods have been reported for the determination of CAP in various samples, including gas chromatography (GC), gas chromatography-mass spectrometry (GC-MS), chemiluminescent, flow injection analysis (FIA), and high performance liquid chromatography (HPLC). However, most of these methods needs expensive apparatus and reagen. Electrochemical methods are widely used in analytical chemistry because they are simple, fast, and low cost. In this study we developed a voltammetry method using carbon paste electrode (CPE) modified with Molecularly Imprinted Polymer (MIP) for determination of CAP in eye drops samples. The modified CPE was made through electropolimerization of methyl red on CPE surface using cyclic voltammetry technique from solution of methyl red and CAP in phosphate buffer. The determination of CAP was carried out by square wave voltammetry. This electrode showed a linear response in concentration range of 0.001 mM - 0.1 mM with detection limit of 0.077 μM. The measurement reproducibility of 0.10 mM and 0.50 mM CAP solution has relative standard deviation of 5.96% and 5.12%, respectively (n=20). The sensor was succesfully applied for the determination of CAP in eyedrops samples with percent recovery between 98.71% - 100.42%.